Descartes and Hume on I-thoughts - Forgione, Luca (THÉMATA. Revista de Filosofía, 2018)
Self-consciousness can be understood as the ability to think "I"-thoughts. More specifically, the notion of self-consciousness that will be considered here can be referred to as basic self-consciousness. This possesses two specific correlated features, analysed in paragraph 1, which are not owned by the consciousness of things other than oneself: the first regards the fact that self-consciousness is grounded on a first-person perspective, whereas the second concerns the fact that it should be considered a consciousness of the self as subject rather than a consciousness of the self as object. Both peculiarities are grounded on the possibility to use the term or concept I which presents a few epistemic and semantic features: the essential indexicality and the immunity to error through misidentification. The first regards the meaning of the term/concept I since any expression of self-awareness is based on indexical terms such as "I" or "me". The second concerns the fact that some singular judgments involving the self-ascription of mental properties are immune to error through misidentification relative to the first-person pronoun. These features will be analysed in paragraph 2 and 3. Paragraph 4, on the other hand, will analyse a few considerations about Descartes and Hume’s approaches to self-consciousness, as both philosophers introduce a first-personal method of accessing the subjective dimension through an introspective account. Descartes’s view on self-consciousness seems incapable of conceiving and recognizing herself as herself, while Hume’s seems to lack those features assigned to the consciousness of self-as-subject.